Impact of the Mycobaterium africanum West Africa 2 Lineage on TB Diagnostics in West Africa: Decreased Sensitivity of Rapid Identification Tests in The Gambia - Ofori-Anyinam, Boatema (PLoS Negl Trop Dis, 2016)
BACKGROUND: MPT64 rapid speciation tests are increasingly being used in diagnosis of tuberculosis (TB). Mycobacterium africanum West Africa 2 (Maf 2) remains an important cause of TB in West Africa and causes one third of disease in The Gambia. Since the introduction of MPT64 antigen tests, a higher than expected rate of suspected non-tuberculous mycobacteria (NTM) was seen among AFB smear positive TB suspects, which led us to prospectively assess sensitivity of the MPT64 antigen test in our setting. METHODOLOGY/PRINCIPAL FINDINGS: We compared the abundance of mRNA encoded by the mpt64 gene in sputa of patients with untreated pulmonary TB caused by Maf 2 and Mycobacterium tuberculosis (Mtb). Subsequently, prospectively collected sputum samples from presumptive TB patients were inoculated in the BACTEC MGIT 960 System. One hundred and seventy-three acid fast bacilli (AFB)-positive and blood agar negative MGIT cultures were included in the study. Cultures were tested on the day of MGIT positivity with the BD MGIT TBc Identification Test. A random set of positives and all negatives were additionally tested with the SD Bioline Ag MPT64 Rapid. MPT64 negative cultures were further incubated at 37°C and retested until positive. Bacteria were spoligotyped and assigned to different lineages. Maf 2 isolates were 2.52-fold less likely to produce a positive test result and sensitivity ranged from 78.4% to 84.3% at the beginning and end of the recommended 10 day testing window, respectively. There was no significant difference between the tests. We further showed that the decreased rapid test sensitivity was attributable to variations in mycobacterial growth behavior and the smear grades of the patient. CONCLUSIONS/SIGNIFICANCE: In areas where Maf 2 is endemic MPT64 tests should be cautiously used and MPT64 negative results confirmed by a second technique, such as nucleic acid amplification tests, to avoid their misclassification as NTMs.